Fragment-Based Screening in Tandem with Phenotypic Screening Provides Novel Antiparasitic Hits. (January 2015) - Blaazer, Antoni R.; Orrling, Kristina M.; Shanmugham, Anitha; Jansen, Chimed; Maes, Louis; Edink, Ewald; Sterk, Geert Jan; Siderius, Marco; England, Paul; Bailey, David; de Esch, Iwan J. P.; Leurs, Rob
Methods to discover biologically active small molecules include target-based and phenotypic screening approaches. One of the main difficulties in drug discovery is elucidating and exploiting the relationship between drug activity at the protein target and disease modification, a phenotypic endpoint. Fragment-based drug discovery is a target-based approach that typically involves the screening of a relatively small number of fragment-like (molecular weight <300) molecules that efficiently cover chemical space. Here, we report a fragment screening on TbrPDEB1, an essential cyclic nucleotide phosphodiesterase (PDE) from Trypanosoma brucei, and human PDE4D, an off-target, in a workflow in which fragment hits and a series of close analogs are subsequently screened for antiparasitic activity in a phenotypic panel. The phenotypic panel contained T. brucei, Trypanosoma cruzi, Leishmania infantum, and Plasmodium falciparum, the causative agents of human African trypanosomiasis (sleeping sickness), Chagas disease, leishmaniasis, and malaria, respectively, as well as MRC-5 human lung cells. This hybrid screening workflow has resulted in the discovery of various benzhydryl ethers with antiprotozoal activity and low toxicity, representing interesting starting points for further antiparasitic optimization.